Gender differences in the perception of dignity among hospitalized older adults - Váverková, Renáta; Kisvetrová, Helena; Bermellová, Jana (Ošetřovatelské perspektivy, 2022)
Background: Given the ageing of the population, it is important to examine the perception of dignity and the factors that may influence it among older adults.Aim: To determine how the perception of dignity and the factors that influence it differ in hospitalized older adult men and women.Methods: A quantitative cross-sectional study was used with a battery of the following questionnaires in their Czech versions: Patient Dignity Questionnaire (PDI-CZ), Geriatric Depression Scale, Attitudes to Ageing Questionnaire, Barthel's Index and Mini-Mental State Examination.Results and discussion: 294 hospitalized older adults participated in the study. In the overall assessment of dignity, men and women did not differ. Differences were confirmed in two PDI-CZ items which were more often perceived as a problem by men, namely: Feeling that I do not have control over my life (p = 0.019) and Feeling that I am not being treated with respect and understanding by others (p = 0.048). It was also shown that the men with higher depression (ß = 2.337, p < 0.0001), a more negative attitude to ageing (ß = -0.481, p = 0.002) and those who did not live alone (ß = 8.379, p = 0.008) had a worse perception of dignity. In women, a lower perception of dignity was associated only with higher depression (ß = 1.99, p < 0.0001) and lower age (ß = -0.311, p = 0.012).Conclusion: The results showed that the only common factor influencing the perception of dignity in both men and women was the level of depression.
Keywords: Depression; senioři; stárnutí; Aging; životní smysluplnost; Inpatients; deprese; Gender Role; postoj; Personhood; důstojnost lidského života; samostatný způsob života; Independent Living; genderová role; Aged; Attitude; Sense of Coherence; hospitalizovaní pacienti